Retrospective study of spontaneous subarachnoid haemorrhage: vasospasm and other complications (Part III) - S. Bakanauskaitė; J. Grigaitė; R. Danilevičienė; G. Lizaitienė; L. Piliponis; J. Ščerbak; D. Jatužis; J. Valaikienė (Neurologijos seminarai)
Background. Acute subarachnoid haemorrhage (SAH) is a dangerous condition: roughly 50% of patients die within 30 days, nearly 25% develop significant neuropsychological and cognitive deficits, about 10% suffer from other complications, and only around 15% recover fully. One of the main causes of mortality is cerebral vasospasm (CVS), a cause of delayed cerebral ischaemia (DCI), which can lead to secondary cerebral infarction. Thus, early detection of CVS is crucial for improving patient outcomes. The aim of this study was to analyse the demographic and clinical (including complications) data of patients diagnosed with SAH, to evaluate the diagnostic methods, and to investigate the prevalence and treatment of complications. Materials and methods. This retrospective study included 102 patients diagnosed with spontaneous SAH, aged at least 18 years, who were treated in the Vilnius University Hospital Santaros Klinikos (VUL SK) in 2014-2017. The obtained VUL SK data were selected by the I60 ICD-10-CM code and depersonalized. Head computerized tomography (CT), CT angiography (CTA), digital subtraction angiography (DSA), transcranial color-coded duplex sonography (TCCS), and magnetic resonance angiography (MRA) were used to evaluate the cerebral arteries. Results. In 102 patients (mean age 58±16 years; 55% female), the most common cause of spontaneous SAH was ruptured aneurysm, the most common arterial sites were the middle cerebral artery (36%), anterior cerebral artery and/or communicating artery (together 33%), and internal carotid artery (20%). In-hospital mortality was as high as 21%. All patients underwent head CT, 78% CTA, 33% DSA, 8% TCCS, and 1% MRA. 71% patients experienced SAH complications: 66% acute, 27% chronic. The most common acute complications were cerebral oedema (34%), rebleeding (29%), and acute ischaemia (23%), the most common chronic complications hydrocephalus (11%), DCI (9%), and CVS (8%). Conclusions. CVS was diagnosed considerably less frequently in this study compared to other studies. While the diagnosis rates of ischaemia and hyponatremia were likewise significantly lower in this study compared to those in others, they are in line with the CVS diagnosis rate. Aside from the CVS and CVS-related complications, all the other SAH complications were roughly within the range of the other studies.